Inheritance Law in Indonesia - Sitti Mashitah Tualeka; Oyo Sunaryo Mukhlas (al-Afkar, Journal For Islamic Studies, 2023)
This study aims to know the development of Islamic inheritance law in Indonesia. Inheritance law is a crucial part of the legal system that governs the transfer of property and rights owned by individuals who have passed away to their heirs. This research employs a document analysis method to investigate the legal regulations and legislations related to inheritance in Indonesia, such as Law No. 5 of 1960 on Basic Agrarian Principles and Law No. 16 of 2019 on Evidence. Additionally, this study involves relevant literature review and case studies to understand the application of inheritance law in Indonesia. The results of this research reveal that the inheritance law system in Indonesia is based on customary, religious, and national law principles. The development of Islamic inheritance law in Indonesia has changed along with changes in the socio-cultural and legal context in this country. Initially, Islamic inheritance law in Indonesia was based on classical fiqh principles based on the texts of the Qur’an and hadith, but overtime there has been an update in Islamic inheritance law. One of the important development in Islamic inheritance law in Indonesia is through the application of a compilation of Islamic law that has been in force sin 1991. The compilation of Islamic law regulates various aspects of Islamic inheritance law which includes the separation of assets, distibution of inheritance, wills and grants.